Role of advanced imaging techniques in cardiac surgery: Aortic dissection. Issue 12 (2nd October 2022) - Paneitz, Dane C.; Hedgire, Sandeep; Jassar, Arminder S.
Abstract: Background : Collaboration among cardiac surgeons and radiologists is essential to fully leverage advanced imaging technologies and improve the care of cardiac surgery patients. In this review, a cardiac surgeon and cardiovascular radiologist discuss imaging pearls and considerations in aortic dissection cases. Methods : The surgeon and the radiologist discuss imaging considerations in two aortic dissection cases. Results : It is essential to obtain and review all phases of a CTA when diagnosing acute aortic pathology. Optimizing scan parameters and careful multiplanar image review is necessary for adept interpretation. Current CT technology allows ECG gating to eliminate motion artifact and allow for dynamic assessment of the aortic pathology. Concurrent evaluation of thoracic aorta and coronary arteries is feasible. A systematic review of the scan using landmarks is critical for appropriate diagnosis and reporting. As TEVAR is increasingly used for arch repair, collaboration with radiologists is essential for preoperative planning in redo cases. Conclusions : Collaboration among cardiac surgeons and radiologists is mutually beneficial for surgeons, radiologists, and their patients.